2003
DOI: 10.1091/mbc.e02-12-0791
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Impairs Normoxic Degradation of HIF-1α by Inhibition of Prolyl Hydroxylases

Abstract: Hypoxia inducible factor-1 (HIF-1) is the master regulator of metabolic adaptation to hypoxia. It is appreciated that HIF-1␣ accumulation is achieved under normoxic conditions by e.g., nitric oxide. We determined molecular mechanisms of HIF-1␣ accumulation under the impact of S-nitrosoglutathione (GSNO). In human embryonic kidney cells GSNO provoked nuclear accumulation of HIF-1␣. This appeared unrelated to gene transcription and protein translation, thus pointing to inhibition of HIF-1␣ degradation. Indeed, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
263
3
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 379 publications
(286 citation statements)
references
References 62 publications
15
263
3
5
Order By: Relevance
“…Under hypoxic conditions, prolyl hydroxylation is reduced, thus finally leading to an increase in HIF-1␣ protein and expression of HIF-1 target genes (9). In addition to hypoxia, which is also a typical feature of the tissue microenvironment during bacterial infection, multiple inflammatory stimuli lead to HIF-1␣ accumulation and activation (10,11). Along with this, an important role of HIF-1 for the host immune response during bacterial infection has recently been shown (12,13).…”
mentioning
confidence: 99%
“…Under hypoxic conditions, prolyl hydroxylation is reduced, thus finally leading to an increase in HIF-1␣ protein and expression of HIF-1 target genes (9). In addition to hypoxia, which is also a typical feature of the tissue microenvironment during bacterial infection, multiple inflammatory stimuli lead to HIF-1␣ accumulation and activation (10,11). Along with this, an important role of HIF-1 for the host immune response during bacterial infection has recently been shown (12,13).…”
mentioning
confidence: 99%
“…In direct contrast to previous findings, some groups found that ρ° cell lines lacking functional mitochondria still stabilize HIFα under hypoxia [76,77]. Other studies suggested that cells with impaired mitochondrial function fail to stabilize HIFα under hypoxia, not because of defective ROS-generation, but because of intracellular O 2 re-distribution which leads to increased availability of O 2 as a substrate for the hydroxylation reaction [72,78]. Although these reports challenge a role for mitochondrial ROS in cellular O 2 sensing, they do not explain why antioxidants, including the recently described mitochondrially-targeted compound MitoQ, block hypoxic HIFα activity [79].…”
Section: Role Of Ros In Cellular O 2 Sensingmentioning
confidence: 83%
“…19,20 Intracellular Fe(II) concentration. NO may inhibit PHD activity by chelating Fe(II) or other mechanisms in addition to the previously mentioned role in promoting PHD activity by oxygen redistribution 21,22 (Figure 2). The net outcome may depend on which effect happens to dominate and is more easily observed under specific experimental conditions.…”
Section: Regulation Of Phd-catalyzed Hydroxylation Reactionsmentioning
confidence: 89%